Comparison of the exponential thermal transient parameterization methods with the SMTP method in the unipedicled DIEP flap computer modelling and simulation. Issue 2 (3rd July 2018) - Moderhak, M.
Abstract: The aim of this paper is to compare the spatial contrast of the image descriptors obtained via three different thermal transient parameterization methods in Active Dynamic Thermography. The thermal constants and amplitude values of the one- and two- exponential parametrization are compared to the Simplified Magnitude-Temporal Parametrization method (SMTP). The comparison is performed using the data obtained by simulating the cold stress ADT exam of the partial computer model of the Deep Inferior Epigastric Perforators (DIEP) skin flap that is used e.g. in one of the breast reconstruction procedures. The results prove that all of the described methods are capable of detecting flap perforators. The SMTP method proved itself as a method with comparable spatial contrast to 1-exponential parametrization. Moreover it has some additional advantages like the excitation of non-uniformity insensitivity and far less computational complexity.